Comparison of Enzyme-Linked Immunosorbent Assay, Western Blotting, Microagglutination, Indirect Immunofluorescence Assay, and Flow Cytometry for Serological Diagnosis of Tularemia - Porsch-Özcürümez, Mustafa (American Society for Microbiology, 2004)
The serodiagnostic efficiencies of five different approaches to detecting antibodies (immunoglobulins G, A, and M) developed in clinically proven infections with Francisella tularensis have been assessed. Fifty serum samples from patients suffering from tularemia during an outbreak in Sweden were compared with samples from 50 healthy blood donors (controls) by using an enzyme-linked immunosorbent assay (ELISA), microagglutination (MA), Western blotting (WB), an indirect immunofluorescence assay (IIFA), and flow cytometry (FC). ELISA, WB, and FC were based on the use of preparations of lipopolysaccharides (LPS) of the live vaccine strain of Francisella tularensis subsp. holarctica (ATCC 29684) as a capture antigen. Whole methanol-fixed bacteria were used for IIFA and MA. Optimized protocols yielded a diagnostic sensitivity and specificity of 100% for WB, MA, and FC, 98% for ELISA, and 93% for IIFA. A total of 6,632 serum samples from individuals between the ages of 18 and 79 years, representatively recruited from all regions of Germany, were screened to estimate and confirm the positive predictive value (PVpos) of the ELISA. Serum samples from 15 (0.226%) individuals tested positive for F. tularensis-specific antibodies by ELISA and confirmatory WB. The resulting prevalence-dependent PVpos of 10.2% and specificity of 98.1% were consistent with our findings for tularemia patients and controls. We conclude that the combined usage of a screening ELISA and a confirmatory WB based on LPS as a common antigen, as well as the MA, is a suitable serodiagnostic tool, while the quality of the IIFA is hampered by subjective variations of the results. FC is a promising new approach that might be improved further in terms of multiplex analyses or high-throughput applications.